AN ANALYZING OF STUDENTSâ€™ EMOTIONALINTELLEGENCE (A Study to the Second Grade Students of PG-PAUD in Academic Year 2011/2012) (Universitas Negeri Semarang, 2012)
This research entitled â€œAn Analyzing of Studentsâ€™ Emotional Intellegence in PG-PAUDâ€, who are going to be a teacher for education for young learners. This is important to build up the characters that should be had to deal with the education world, especially as the teacher for young learners. Beside, the result of analyzing the emotional intelligence will be a reference to do the emotional intelligence development. By using the instrument taken from DR. Baron Reuven, (Makmun Mubayidh, 2006) it has got around 54,5 % of students who has got the highest score in EQ. It has the positivemeaning because the higehest score in EQ will color all their personal and social in living with others along with living as the teacher. The rest is about 45,5 %, of students still need a training continually and also they have many aspects that should be improved to make the emotional running consistently and properly. From ten cases which have beenoffered to students, itâ€™s only two cases that can be solved well. The rest shows about the unbalance emotional. According to both instruments, emotional intelligence for students especially connects with real-life moral dilemmas still need a training regularly. Emotional intelligence training which being a part in improving a good moral need process of choosing, prizing dan behaving (Raths et.al. ,1966) which guide someone totake the decision about the value. Emotional intelligence training through learning needs a lecture that cares about. The appreciation shown by holding the discussion because it will guide to understanding, empathy or respect (Noddings, 2003; Owens & Ennis, 2005); and being a role model (Noddings, 2002; Chen, 2009). Colleague as the place for getting knowledge is the condusive environment for distributing the appreciation by integrating the value of learning in subject matter for improving the emotional intelligence.Â This case should be explicited in order to make studentsâ€™ emotion run properly according to the norm and custom which exist in citizen.